A novel system and method for maxillary protraction in class III malocclusion adult patients - Sheibani Nia, Ahmad (Researcher Bulletin of Medical Sciences, 2023)
Background and Objectives: Given the extensive number of surgical procedures available for correcting CL III anomalies, the present study was conducted in a private clinic from 2014-15 to determine whether simpler orthodontic and surgery techniques could be an alternative to the conventional techniques for resolving such functional and aesthetic problems. Materials and Methods: The present study was conducted using a sequential before-after design on patients with mild to moderate maxillary deficiency. First, the study records including casts, photographs and radiographs were prepared. A Hyrax appliance with two tongue plates was then constructed for the patient before the Surgically Assisted Rapid Maxillary Expansion (SARME) osteotomy. The surgical technique involved local anesthesia without general anesthesia and the Lefort I osteotomy was performed without down fracture and without the manipulation of the pterygomaxillary suture. The transverse problem was corrected by unscrewing the Hyrax, and the tongue force exerted on the back of the tongue plate corrected the sagittal maxillary deficiency. To evaluate the efficacy of this appliance, the mean changes to the cephalometric indicators before and after the treatment were examined, and the paired t-test was used for the statistical analysis. Results: The present study was conducted on 11 patients (9 females and 2 males). The mean changes indicated a significant increase in Articular Angle, Jarabak index, and a significant decrease in L1 - NB (mm), L1 - NB (º) and Saddle Angle. The other indicators had either decreased or were not changed. Conclusion: Using a Hyrax appliance combined with a tongue plate after a SARME surgery is effective in correcting CL III anomalies associated with maxillary deficiency.